IMPLEMENTASI PROGRAM DOUBLE TRACK SEBAGAI PENGUATAN PENDIDIKAN KARAKTER MANDIRI DAN TANGGUNG JAWAB PESERTA DIDIK SMAN 1 CAMPURDARAT - Lafifah, Shofia; Nanik Setyowati, Raden Roro (Universitas Negeri Surabaya (Unesa), 2024)
Juvenile delinquency cases are indeed a complex problem for students. Efforts to minimize it through strengthening independent character education and responsibility. SMAN 1 Campurdarat is a school that implements the Double Track program in Tulungagung Regency by not only focusing on skill formation but also strengthening independent character and responsibility. The purpose of this study is to determine how the implementation of the Double Track program in strengthening and its obstacles. This study uses a qualitative approach with a case study method. The collection technique is by interview, observation, and documentation. The data analysis technique for this study is based on Miles and Huberman which consists of four stages, namely data collection, data reduction, data presentation and drawing conclusions. The theoretical basis for this study is the theory of character formation by Thomas Lickona. In the research results there is a classification of the form of activities in strengthening independent character, namely (1) skills provision activities through the process of delivering material or skills; (2) skills development activities are shown by carrying out an update or innovation on the material that has been given during skills provision; (3) product management activities by packaging, labeling, and conducting market analysis. While in the character of responsibility, namely; (1) continuous skills provision activities are located when distributing KUS; (2) monitoring and evaluation activities carried out by trainers and the ITS team; (3) product marketing through Ramadan festivals, direct exhibitions and DUDI cooperation.